2009
DOI: 10.2146/ajhp080065
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity in patients treated with intravenous polymyxin B: Two case reports

Abstract: Two patients developed symptoms of neurotoxicity after receiving intravenous polymyxin B for the treatment of MDR gram-negative infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The emergence of drug-resistant P. aeruginosa strains, which exhibit increased MICs even for polymyxin B (PMB) (10), requires the development of effective dual-and triple-drug combinations for medical treatment of these infections (7,11). Despite the high effectiveness of polymyxins, the neuro-and nephrotoxicity associated with this treatment, especially during intravenous administration, increase the risk of using this drug (12,13). However, daily subcutaneous administration of polymyxins resulted in decreased nephrotoxicity (14,15), and inhaled polymyxin E, better known as colistin, showed no adverse effects (16).…”
mentioning
confidence: 99%
“…The emergence of drug-resistant P. aeruginosa strains, which exhibit increased MICs even for polymyxin B (PMB) (10), requires the development of effective dual-and triple-drug combinations for medical treatment of these infections (7,11). Despite the high effectiveness of polymyxins, the neuro-and nephrotoxicity associated with this treatment, especially during intravenous administration, increase the risk of using this drug (12,13). However, daily subcutaneous administration of polymyxins resulted in decreased nephrotoxicity (14,15), and inhaled polymyxin E, better known as colistin, showed no adverse effects (16).…”
mentioning
confidence: 99%
“…Several antibiotic classes, including polymyxins and aminoglycosides, are known to be associated with neuromuscular blockade [4,7]. Polymyxin B causes a non-competitive neuromuscular blockade that is not responsive to cholinesterase inhibitors [2,5], leading to respiratory arrest as in our case. No known treatments exist beyond supportive care such as mechanical ventilation.…”
Section: Discussionmentioning
confidence: 86%
“…They are used to treat severe multidrug-resistant (MDR) gram-negative infections [2,3,5,6]. As the rates of MDR infections continue to rise worldwide, there is a concomitant resurgence in the use of antimicrobial agents typically seen as last-line therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobieszczyk et al [58] reported neuropathy manifesting as seizures and neuromuscular weakness which were possibly related to polymyxin B in two (7%) cases. Weinstein et al [59] recently reported two cases of polymyxin B induced neuropathy. First case was 60-year-old obese diabetic female with other multiple ailments and was on treatment with multiple medication including varenicline and quetiapine.…”
Section: Efficacy Of Polymyxin B: Combination Therapymentioning
confidence: 99%